Arkansas and the New South, 1874-1929 - Moneyhon, Carl H., 1944- (Histories of Arkansas., 1997)
This study is the first published in the Histories of Arkansas, a new series that will build a complete chronological history of the state from the colonial period through modern times. Under the general editorship of noted historian Elliott West, this series will include various thematic histories as well as the chronologically arranged core volumes. In Arkansas and the New South, 1874-1929 Carl Moneyhon examines the struggle of Arkansas's people to enter the economic and social mainstreams of the nation in the years from the end of Reconstruction to the beginning of the Great Depression. E.